1979
DOI: 10.1071/bi9790237
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Frozen-Thawed Boar Semen

Abstract: Exposure of male CSF rats to a signalled unpredictable 60-day stress regimen induced a significant elevation in circulating triiodothyronine (T 3) concentration above the control for the first 20 days of stress before the rate of secretion returned to normal. On the other hand, circulating thyroxine (T 4) concentration fell significantly below the control value for the first 5 days of stress before the normal rate of secretion was reached by 10 days. A histological study of the thyroid gland revealed no change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous studies have also not found differences between temperatures of CPA addition on sperm quality (Maxwell and Salamon, 1979; Cochran, 1984). However, it has been reported in several species that the temperature of the addition of the CPAs can affect post‐thaw sperm quality (Salisbury et al, 1978; Parks and Lynch, 1992; Sieme et al, 1998; McGonagle et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have also not found differences between temperatures of CPA addition on sperm quality (Maxwell and Salamon, 1979; Cochran, 1984). However, it has been reported in several species that the temperature of the addition of the CPAs can affect post‐thaw sperm quality (Salisbury et al, 1978; Parks and Lynch, 1992; Sieme et al, 1998; McGonagle et al, 2002).…”
Section: Discussionmentioning
confidence: 86%